Gastrostomy as a Preemptive Measure after Pancreatoduodenectomy against Delayed Gastric Emptying: A Small Case Series and a Review of the Literature. (23rd February 2021) - Floros, G.; Galanis, I.; Theodoropoulos, P.; Bartziotas, D.; Theodoropoulos, C.; Metaxa, M.; Giannos, G.; Tsintavis, P.; Stylianidis, G.; Klimopoulos, S.
Abstract : Delayed gastric emptying (DGE) is a common (20–30%) postoperative complication following pancreatoduodenectomy (PD) (Parmar et al., 2013). Various causes and preemptive measures have been suggested to decrease the occurrence of DGE. We added a simple step in the procedure of 26 consecutive pancreatic head resections, which seems to alleviate DGE and has never been highlighted before.